β-Aminoisobutyric Acid Relates to Favorable Glucose Metabolism through Adiponectin in Adults with Obesity Independent of Prediabetes - Habiba Faiz; Emily M. Heiston; Steven K. Malin (Journal of Diabetes Research)
β-Aminoisobutyric acid (BAIBA) is secreted by skeletal muscle and promotes insulin sensitivity, fat oxidation, and anti-inflammation. While BAIBA is purportedly lower in individuals with obesity, no work has examined if prediabetes (PD) differentially impacts BAIBA concentrations in people with obesity. Methods. Adults were classified as normal glucose tolerant (NGT; n=22 (20F); 48.0±2.4 yrs; 36.9±1.2 kg/m2) or PD (n=23 (18F); 54.2±1.6 yrs; 38.4±1.2 kg/m2) based on ADA criteria. A 180-minute 75 g OGTT was used to estimate fasting (HOMA-IR (liver)) and postprandial (Matsuda index (muscle)) insulin sensitivity as well as β-cell function (disposition index (DI), glucose-stimulated insulin secretion adjusted for insulin sensitivity). Body composition and fasting measures of BAIBA, fat oxidation (indirect calorimetry), and adipokines were determined. Results. NGT and PD had similar BAIBA concentrations (1.4±0.1 vs. 1.2±0.1 μM, P=0.23) and fat oxidation (P=0.31), despite NGT having lower fasting (92.2±1.2 vs. 104.1±3.2 mg/dL, P=0.002) and tAUC180min glucose (P<0.001) compared to PD. Moreover, NGT had higher postprandial insulin sensitivity (P=0.01) and higher total phase DIliver (P=0.003) and DImuscle (P=0.001). Increased BAIBA was associated with adiponectin (r=0.37, P=0.02), adiponectin/leptin ratio (r=0.39, P=0.01), and lower glucose and insulin at 180 minutes (r=−0.31, P=0.03 and r=−0.39, P=0.03, respectively). Adiponectin also correlated with lower glucose at 180 minutes (r=−0.45, P=0.005), and mediation analysis showed that BAIBA was no longer a significant predictor of glucose at 180 minutes after controlling for adiponectin (P=0.08). Conclusion. While BAIBA did not differ between NGT and PD, higher BAIBA is related to favorable glucose metabolism, possibly through an adiponectin-related mechanism. Additional work is required to understand how exercise and/or diet impact BAIBA in relation to type 2 diabetes risk.